Reduksi Noise Citra Magnetic Resonance Imaging Pemeriksaan Cervical dengan Teknik Denoising Weighted Median Filter (WMF) untuk Peningkatan Kualitas Citra - Annisa, Aulia; Marliana; Desti Monika Uli (Jurnal Imejing Diagnostik (JImeD), 2026)
Background: Magnetic resonance imaging (MRI) is a non-invasive method that is crucial for diagnosing various medical conditions, including cervical MRI. However, one of the challenges often encountered in MRI image analysis is the presence of noise, which can compromise image quality. Noise in MRI images can suppress important details, impede diagnostic accuracy, and increase the likelihood of misinterpretation. One technique that has been proven effective in reducing image noise is the Weighted Median Filter (WMF). This research is crucial for improving the diagnostic quality of MRI images. The aim of this research is to determine the differences and assess the image quality between before and after applying the Weighted Median Filter (WMF) denoising technique to Cervical MRI images. Methods: In Cervical MRI images, image information was improved using the Weighted Median Filter (WMF) denoising technique to produce images with better quality. Each image was measured for image information before and after the denoising technique. Image information was assessed in two ways: image quality (SNR and CNR), and filter performance (PSNR and MSE). Results: Based on the results of the difference test, there is a difference in the quality of the SNR and CNR images between before and after the WMF denoising technique. And the results of the filter performance test produce good values that are still within standard limits. Conclusions: that there is a significant difference between the image before reduction and the image after reduction with WMF denoising technique. In this research, the MRI Cervical image of T1 GRE axial slice sequence produces a good filter performance assessment (PSNR and MSE) and also for the image quality before and after the denoising technique produces SNR and CNR that are in line, namely there is an increase in image quality between before and after WMF technoising.